Pengaruh Persepsi, Efikasi Diri Dan Budaya Kerja Terhadap Kinerja Pegawai di Kantor BPJS Ketenagakerjaan Kota Singaraja - I Made Mai Noval; Ni Luh Sri Kasih; Pande Putu Eka Indra Cahyan (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2025)
This study aims to determine the effect of perception, self-efficacy and work culture on employee performance at the BPJS of Employment Office in Singaraja City. The population in the study was 33 people while the sample in this study was a saturated sample, in which the entire population acted as a sample. Data collection method by using a questionnaire technique data analysis techniques using the SPSS Version 20 application for windows. The results showed that: 1) Perception has a direct and significant positive effect on employee performance at the Singaraja City Employment BPJS office, 2) Self-efficacy has a direct and significant positive effect on employee performance at the Singaraja City Employment BPJS office, 3) Culture work affects the performance of employees at the Employment BPJS office in Singaraja City.